Vaporizing foil actuator welding technique for dissimilar joining of AA3003 and SS321 - Су Shan; Цхен Shujun; Xиао Jun; Мао Yu; Анупам Vivek; Даехн Glenn (Materials. Technologies. Design, 2019)
Vaporizing foil actuator welding (VFAW), a novel solid-state welding method was applied for the dissimilar lap welding of 3003 aluminium alloy and 321 stainless steel sheets. Three input energy with a 2.5mm thick of flyer and target were used (4, 6 and 8 kJ) in AA3003/321 VFAW process. SEM and EDS were used to obtain the morphology and element distribution in the interface. The result shows that the flyer workpiece and the tensile strength can get higher velocity with input energy increased. The bonding region length increased and the thick of IMC layer decreased with input energy increased. This study demonstrates VFAW’s capability in welding 3003 aluminium alloy and 321 stainless steel, which is widely used in the aerospace, chemical, defence and aviation industries.